CAUSALES PARA LA DESTITUCIÓN AL RECTOR (A) Y VICERRECTORES (AS) EN LA LEY ORGÁNICA DE EDUCACIÓN SUPERIOR - Capelo Naula, Verónica Gabriela (2019)
The present Thesis is the final report of the research process motivated, in virtue of the need to increase causes of dismissal to the Rector (a) and Vice Rectors (as) in the Organic Law of Higher Education; since within the Organic Law of Higher Education there are only sanctions against the institutions as such, but not those directly responsible for the irregular acts committed in the exercise of their function. Therefore, I consider that the Organic Law of Higher Education should include the dismissal of the Rector (a) and Vice Rectors (as), in order to have legal security and an expeditious and expeditious process for its sanction. This thesis contains conceptual references and doctrinal elements that allow the understanding of the legal problematic; based on the data collected from legal experts, as well as the citizens who have lived through the latent problem, and as a result of this investigative process, allowed me to formulate as a legal proposal: the increase of grounds for the dismissal of the Rector (a) and Vice Rectors (as) in the Organic Law of Higher Education.